CONTENT ANALYSIS PEMBERITAAN PARTAI POLITIK ISLAM DI PEMILU LEGISLATIF 2014 - Dedi Syahputra (Program Pascasarjana UIN Sumatera Utara, 2016)
To reach a wider audience, the mass media with the sporadic nature, heterogenic, and anonymous, is an effective tool to be used as a communication channel. Islamic political parties in legislative elections in 2014 have the benefit of disseminating information widely on political campaigns through the mass media. This study investigated the interaction of Islamic political parties in North Sumatra with the mass media by using content analysis (content analysis) news media (Daily Alert and Analysis) of the Islamic political party (PKS and PPP) in the 2014 legislative election campaign in North Sumatra. The results show that the interaction of Islamic political parties in the media is not maximized. MCC looks more aggressive otherwise PPP tend not to take any action in the design of political communication through the mass media.